Development of Tactil Audio Media For Low Vision Students - Mu'jizatin Fadiana; Ifa Seftia Rakhma Widiyanti; Saeful Mizan (Department of Special Education, 2022)
This study aims to develop a valid and effective audio tactile learning media to improve the learning achievement of students with visual impairments, especially low vision. The development model used is the 4D model (Define, Design, Develop, and Disseminate). Data collection techniques include observation, interviews, documentation, and tests. This study uses a quantitative approach as a data analysis technique. The product developed is a set of learning media consisting of audio media and tactile media for mathematics statistics courses. Audio media in the form of power point video containing sound and supported by several tactile media such as colored dice, coins, colored coins, number cards, bridge cards and colored cubes. The results of expert validation tests carried out on the developed instruments are categorized as valid and effective.